Characterisation of the bioactive behaviour of sol-gel hydroxyapatite-CaO and hydroxyapatite-CaO-bioactive glass composites - Hatzistavrou, E.; Chatzistavrou, X.; Papadopoulou, L.; Kantiranis, Nikolaos; Kontonasaki, E.; Boccaccini, Aldo R.; Paraskevopoulos, K. M. (Materials Science and Engineering C, 2010)
The fabrication and characterization of sol-gel derived hydroxyapatite-calcium oxide (HAp-CaO) material is investigated focusing on the effect of the addition of a bioactive glass on the material bioactive behaviour through the fabrication of a novel HAp-CaO (70 wt.%)-bioactive glass (30 wt.%) composite material. The bioactive behaviour of the materials was assessed by immersion studies in Simulated Body Fluid (SBF) and the alterations of the materials surfaces after soaking periods in SBF were characterized by Scanning Electron Microscopy (SEM) and Fourier Transform Infrared Spectroscopy (FTIR). A brittle and weakly crystalline carbonate hydroxyapatite (HCAp) layer was found to develop on the surface of all samples, few hours after immersion in SBF, confirming the high bioactivity of the material. Alterations of the morphology of the developed HCAp layer, which led to a more compact structure, were observed on the surface of composite samples after 7 days of immersion in SBF. The presence of the CaO phase seems to accelerate the formation of HCAp, while the bioactive glass affects both the morphology and cohesion of the developed layer. © 2010 Elsevier B.V. All rights reserved.
UnivIS-Import:2015-03-09:Pub.2010.tech.IW.LM.charac_3
Keywords: Bioactive glass; Bone regeneration; HAp-CaO; Simulated body fluid; Sol-gel method